2014
DOI: 10.5137/1019-5149.jtn.11499-14.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of montelukast on spinal cord ischemia/reperfusion injury

Abstract: AIm: Paraplegia due to ischemia-reperfusion (I/R) injury of the spinal cord is a devastating complication of thoracoabdominal aortic surgery. Cysteinyl leukotrienes are potent mediators of inflammation that are associated with I/R injury. The present study was designed to investigate the role of montelukast, a selective reversible CysLT1 receptor antagonist, on spinal cord I/R injury in an experimental model. mAterIAl and methOds: Twenty-one male Sprague-Dawley rats were randomly assigned to three groups (n=7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Motor deficit index data evaluations suggested that administering CAR 48 h after an injury reduced motor function capacity (MFC). Many studies in the literature showed that MFC was an important parameter for the evaluation of SIR (Badem et al, 2014;Erkut and Onk, 2015;Korkmaz et al, 2015;Liang et al, 2011). Some studies used motor function evaluation methods similar to those used in the current study (Ryu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Motor deficit index data evaluations suggested that administering CAR 48 h after an injury reduced motor function capacity (MFC). Many studies in the literature showed that MFC was an important parameter for the evaluation of SIR (Badem et al, 2014;Erkut and Onk, 2015;Korkmaz et al, 2015;Liang et al, 2011). Some studies used motor function evaluation methods similar to those used in the current study (Ryu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Korkmaz et al (2015),which investigatedthe effects of CysLT1 receptor antagonist montelukast following SIR, MDI was evaluated for MFC scoring. In other studies, MFC scoring following SIR was performed by Tarlov scale (Erkut and Onk, 2015;Guven et al,2015) or Basso, Beattie, and Bresnahan (BBB) scoring (Basso et al, 1995;, which uses 21-point scoring to determine the activity of an animal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Montelukast has displayed antioxidant and anti-inflammatory effects in various diseases. Montelukast has been shown to improve motor recovery and reduce IL-6 levels in spinal cord ischemia-reperfusion (I/R) injury [6]. Another study demonstrated that administration of montelukast decreased respiratory syncytial virus-induced mucus hyperproduction in a rodent in vivo model [7].…”
Section: Introductionmentioning
confidence: 99%